Visual communication in Brazilian species of anurans from the Atlantic forest - Hartmann, M. T.; Giasson, LOM; Hartmann, P. A.; Haddad, CFB (Taylor & Francis Ltd, 2005)
Visual communication is widespread among several anuran families, but seems to be more common than currently thought. We investigated and compared visual communication in six species of an anuran community in the Brazilian Atlantic forest. Four are nocturnal species: Hyalinobatrachium uranoscopum (Centrolenidae), Hyla albomarginata, Hyla sp. (aff. ehrhardti), and Scinax eurydice (Hylidae), and two are diurnal species: Hylodes phyllodes and Hylodes asper ( Leptodactylidae). For H. uranoscopum, H. albomarginata, S. eurydice, and H. phyllodes, this is the first record of visual communication. Observations were made at Nucleo Picinguaba, Parque Estadual da Serra do Mar, in the Municipality of Ubatuba, State of São Paulo, Brazil. Descriptions of behaviour were based on individuals observed in the field, using sequence sampling with continuous tape recording for behavioural observations. Eight new behaviours are described: body wiping, face wiping, jump display, leg kicking, limb lifting, mouth opening, toe flagging, and vocal sac display. of the 42 anuran species known from Nucleo Picinguaba, at least six ( approximately 14%) display visual communication. The evolution of visual signals in these species may be related to the availability of ambient light, the structural complexity of the habitat, and/or the ambient noise. They may also have evolved to aid in the location of the individual, to avoid physical combat, and/or may be a by-product of seismic communication.
Keywords: anuran; Atlantic forest; behaviour; Hyalinobatrachium; Hyla; Hylodes; Scinax